CHEMICAL STUDY OF LAVANDULA FERTILIZER - A.B. Tashimbetova; A.K. Umbetova; Z.B. Halmenova; Y.S. Ikhsanov; M.I. Choudhary; Zh.A. Abilov; G.Sh. Burasheva (Academic Scientific Journal of Chemistry, 2020)
Genus Lavandula – specially grown as an aromatic and medicinal plant. In inflorescences, the content of essential oil is from 0.8 % to 2.6 %, in leaves up to 0.3 %. The main components of the essential oil are linalool (10-30 %) in the free state and its esters with acetic, butyric, valerianic, caproic acids (30-60 %), as well as geraniol, citral, borneolen, bisabolene, α-pinene and others. Currently, the plant is used as an ornamental, as a spice in cooking, as well as for medicinal purposes. In traditional medicine, flowers, leaves and branches of lavender are used. In Bulgaria, lavender is used as a means of calming the nervous system, relaxing baths and for skin diseases. In Germany, ointments are made from lavender petals. In Austria, lavender leaves are collected before flowering and are used as soothing and anti-inflammatory drugs. In Poland, in combination with a pharmacy chamomile flower, the flowers of a lavender plant are used in the healing of a fresh voice and bronchial disease. In France, an infusion of lavender flowers is used as an urolithic substance. The object of the study is raw materials L.angustifolia of individual collection at the experimental site of the laboratory of medicinal plants of the Institute of Phyto-Introduction and Botany at the Ministry of Science and Education of the Republic of Kazakhstan of Almaty. The technology for producing a biologically active complex from the plant species under study has been developed by varying the nature of the extractant, its ratio with raw materials, time and extraction ratio. The optimal condition for obtaining a biologically active complex from a plant is: extractant – 50 % ethyl alcohol, the ratio of extractant to raw material – 1: 9, the time of double extraction – 72 hours, temperature – 25 ºC. The fractional composition of the aerial mass of L.angustifolia, which is represented by water-soluble and water-insoluble fractions, was studied. The article presents for the first time the data of a qualitative and quantitative analysis of the lipophilic components of the aerial mass of L.angustifolia, determined by gas-liquid chromatography with mass spectrometry (GC / MS). Analyzes were carried out in a laboratory of chemistry of natural coefficients, University of Karachi, Karachi, Pakistan, the structure and quantitative content of 16 compounds were established in the aerial mass of the plant L.angustifolia. The identification of the components was carried out by analogy with the known mass spectra of the samples embedded in the computer data bank and relative retention times. Quantitative determination of the composition of the analyzed mixture was carried out by the method of normalization by peak areas